Classification et utilisations possibles du betail "non conventionel" - Peters, Kurt J. (1987)
Classifies unconventional livestock according to size, ecological affinity and economic importance and discusses their use in systems with limited production resources, their complementarity with conventional livestock, and the potential of multipurpose species for specialized production of products vital for the sustenance of the human population.